EPISTEMOLOGI TAFSIR MULLÄ€ á¹¢ADRÄ€ - Kerwanto, Kerwanto (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
This article aims to carry out an exploration related to the epistemological setting of MullÄ á¹¢adrÄ's interpretation. Apart from being known as the main Muslim philosopher as Ibn SinÄ, á¹¢adrÄ also describes his mystical-philosophical views in his collection of commentary treatises, TafsÄ«r al-QurÄn al-KarÄ«m. Through this article, the author describes a set of interpretive epistemologies used by á¹¢adrÄ, which can be used as an epistemological offer to bridge several issues of Sufi interpretation (tafsÄ«r al-ishÄrÄ«), especially in the validity of its disclosure method. In addition to the method of interpretation, there are other unique things contained in this article, such as: mukÄshafah as the main foundation of interpretation as it applies generally in the Sufi interpretation (tafsÄ«r al-ishÄrÄ«), sources of interpretation (maá¹£Ädir al-tafsÄ«r) and the style of explanation of the commentary (uslÅ«b al-tafsÄ«r) that á¹¢adrÄ uses. Furthermore, to complete this paper, the author also describes á¹¢adrÄ's view of the ontology of the Quran as the basis of his interpretation epistemology.